2019
DOI: 10.31788/rjc.2019.1225115
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of New and Known Compounds Prepared From Eugenol

Abstract: Eugenol and its new or known derivatives were prepared through varies reactions and screened by in vitro model of antibacterial activities using pathogen bacteria: Eschericia coli, Bacillus cereus, and Staphylococcus aureus. Nearly all compounds showed antibacterial activities. The obtained results demonstrate that eugenol was still significantly more active than its derivatives, with inhibition (14-18) mm, suggesting that this chemical transformation failed to increase antibacterial activities of eugenol. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…With a combination of other active components of the oil, this compound has been reported to have antioxidant activity, anti-inflammatory and antimutagenic 14 . The compound is relatively similar in terms of chemical structure to the eugenol family, a group of a compound that has a significant effect against bacteria 15 .…”
Section: -mentioning
confidence: 99%
“…With a combination of other active components of the oil, this compound has been reported to have antioxidant activity, anti-inflammatory and antimutagenic 14 . The compound is relatively similar in terms of chemical structure to the eugenol family, a group of a compound that has a significant effect against bacteria 15 .…”
Section: -mentioning
confidence: 99%
“…One of these natural substances is eugenol. Eugenol is the main ingredient extracted from the leaves and buds of Eugenia cariophyllata (clove), which belongs to the family Myrtaceae [ 14 ]. It has been demonstrated that eugenol EOs may be used in a wide range of sectors, including agriculture, flavorings, food, cosmetics, and medicines.…”
Section: Introductionmentioning
confidence: 99%